Monetary Policy in Disaster-Prone Developing Countries - Cantelmo, Alessandro (IMF Working Papers; Working Paper, 2022)
This paper analyzes monetary policy regimes in emerging and developing economies where climate-related natural disasters are major macroeconomic shocks. A narrative analysis of IMF reports published around the occurrence of natural disasters documents their impact on important macroeconomic variables and monetary policy responses. While countries with at least some degree of monetary policy independence typically react by tightening the monetary policy stance, in a sizable number of cases monetary policy was accommodated. Given the lack of consensus on best practices in these circumstances, a small open-economy New-Keynesian model with disaster shocks is leveraged to evaluate welfare under alternative monetary policy rules. Results suggest that responding to inflation to an extent sufficient to keep inflation expectations anchored, while allowing temporary deviations from its target is the welfare maximizing policy. Alternative regimes such as strict inflation targeting, exchange rate pegs, or Taylor rules explicitly responding to economic activity or the exchange rate would be welfare-detrimental.